Fragment-Based Quantum Mechanical Calculation of Excited-State Properties of Fluorescent RNAs - Shen, Chenfei; Wang, Xianwei; He, Xiao (Frontiers in Chemistry, 2021)
Fluorescent RNA aptamers have been successfully applied to track and tag RNA in biological system. However, it is still challenging to predict the excited-state properties of the RNA aptamer-fluorophore complex with the traditional electronic structure methods due to expensive computational cost. In this study, an accurate and efficient fragmentation quantum mechanical (QM) approach of the Electrostatically Embedded Generalized Molecular Fractionation with Conjugate Caps (EE-GMFCC) scheme was applied for calculations of excited-state properties of the RNA aptamer-fluorophore complex. In this method, the excited-state properties were first calculated with one-body fragment quantum mechanics/molecular mechanics (QM/MM) calculation (the excited-state properties of the fluorophore), and then corrected with a series of two-body fragment QM calculations for accounting for the QM effects from the RNA on the excited-state properties of the fluorophore. The performance of the EE-GMFCC on prediction of the absolute excitation energies, the corresponding transition electric dipole moment (TEDM) and atomic forces at both the TD-HF and TD-DFT levels was tested using the Mango-II RNA aptamer system as a model system. The results demonstrate that the calculated excited-state properties by EE-GMFCC are in excellent agreement with the traditional full-system time-dependent ab initio calculations. Moreover, the EE-GMFCC method is capable of providing accurate predication of the relative conformational excited-state energies for different configurations of the Mango-II RNA aptamer system extracted from the molecular dynamics (MD) simulations. The fragmentation method further provides a straightforward approach to decompose the excitation energy contribution from per ribonucleotide around the fluorophore, and then reveals the influence of the local chemical environment on the fluorophore. The applications of EE-GMFCC in calculations of excitation energies for other RNA aptamer-fluorophore complexes demonstrate that the EE-GMFCC method is a general approach for accurate and efficient calculations of excited-state properties of fluorescent RNAs.